Maternal and neonatal outcome in cases of premature rupture of membranes beyond 34 weeks of gestation - Sharma, Sanjay Kumar; Dey, Madhusudan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preterm premature rupture of membrane (PPROM) and premature rupture of membrane (PROM) are associated with various maternal and neonatal complications. Management guidelines regarding rupture of membrane before labour is still controversial. The study was carried out to determine the various maternal and neonatal outcomes associated with rupture of membranes beyond 34 weeks of gestation. Methods: It was a prospective observational study carried out in a tertiary care teaching hospital for a period of one year. All the pregnant women with rupture of membrane beyond 34 weeks are included in the study. After establishment of diagnosis of rupture of membranes, antibiotics were started and all of them were induced after 6 hours if they did not have spontaneous labour. Various maternal and neonatal outcomes were noted and statistical analysis carried out. Results: Incidence of rupture of membrane in our study was 4.2%. 92% of patients delivered within 24 hours of rupture of membrane and 18% of them required caesarean section. 5 neonates had respiratory distress syndrome and 1 neonate had sepsis. Conclusions: Induction of labour and delivery within 24 hours of rupture of membranes associated with low incidence of maternal and neonatal adverse outcome.